Exploring the Relationship Between Visual Aesthetics and Social Commerce Through Visual Information Adoption Unimodel - Yang, Yongzhong; Tang, Yunyan; Zhang, Yu; Yang, Ruo (Frontiers in Psychology, 2021)
The visual revolution and attention economy in the digital world have put visual aesthetic communication into the primary position of social commerce practices. However, this phenomenon remains under explored within social commerce research. This study thus develops a visual information adoption unimodel to explore the relationship between visual aesthetics and social commerce intentions. Users with social commerce experience are invited to complete our online survey, and 321 valid data are collected. The results reveal that visual aesthetic has direct and indirect (via perceived usefulness) effects on users’ social commerce intention. Besides, self-construal will moderate these effects in which interdependent self-construal strengthen the positive effect between visual aesthetic and social commerce intention, while independent self-construal weaken the mediation effects of perceived usefulness. Based on the findings, this study will provide important theoretical and practical implications for social commerce, visual communication and cognitive psychology literatures.